2016
DOI: 10.1053/j.gastro.2016.07.031
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation-Induced Expression and Secretion of MicroRNA 122 Leads to Reduced Blood Levels of Kidney-Derived Erythropoietin and Anemia

Abstract: BACKGROUND AIM Anemia is commonly associated with acute and chronic inflammation, but the mechanisms of their interaction are not clear. We investigated whether microRNA 122 (MIR122), which is generated in the liver and is secreted into the blood, is involved in the development of anemia associated with inflammation. METHODS We characterized the primary transcript of the human liverspecific MIR122 using northern blot, quantitative real-time PCR, and 3' and 5' RACE analyses. We studied regulation of MIR122 in h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
43
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(52 citation statements)
references
References 47 publications
7
43
0
Order By: Relevance
“…Instead, evidence suggests that miR‐122 can be released actively from the liver, at least in part within extracellular vesicles, in response to stress . For example, it has recently been shown that in response to stimuli and in the absence of overt hepatocyte death, miR‐122 can be released and can modulate activation of innate immune cells or directly regulate kidney release of erythropoetin . Therefore, the variability that is inherent to miR‐122 levels not only between individuals but also within the same individual likely results from physiologic processes unrelated to damage to the liver.…”
Section: Discussionmentioning
confidence: 99%
“…Instead, evidence suggests that miR‐122 can be released actively from the liver, at least in part within extracellular vesicles, in response to stress . For example, it has recently been shown that in response to stimuli and in the absence of overt hepatocyte death, miR‐122 can be released and can modulate activation of innate immune cells or directly regulate kidney release of erythropoetin . Therefore, the variability that is inherent to miR‐122 levels not only between individuals but also within the same individual likely results from physiologic processes unrelated to damage to the liver.…”
Section: Discussionmentioning
confidence: 99%
“…miR-29b is repressed by NF-κB pathway [24], and miR-29b can repress TNFAIP3, a negative regulator of NF-κB pathway [25]. LPS induced inflammation increases blood levels of miR-122 [26]; serum miR-122 also correlates with mortality in human sepsis patients [27, 28]. miR-125b is down-regulated in bovine CD14+ monocytes stimulated with Staphylococcus aureus enterotoxin B [29] and activate the NF-κB pathway by targeting TNFAIP3 [30].…”
Section: Introductionmentioning
confidence: 99%
“…However, the association of TNF-α with the protective effect of Epo on the kidney, which has been shown in many different studies, was shown in vivo for the first time in the present study. A different approach by Rivkim et al, who blocked microRNA-122, indicating that this microRNA is the responsible element for depressing Epo synthesis during inflammation [10]. We blocked TNF-α with an antibody, which is used for the treatment of chronic inflammatory diseases, and increased the level of Epo with a simpler approach than that used by Rivkim et al…”
Section: Discussionmentioning
confidence: 99%
“…La Ferla et al reported that this effect was achieved via nuclear factor (NF)-κB [9]. A more recent study by Rivkin et al showed the inhibition of Epo synthesis by NF-κB and TNF-α in different in vivo and in vitro models [10].…”
Section: Introductionmentioning
confidence: 99%